Use of multimedia technologies during distance learning in higher education institutions - Nadya Riznyk (Hryhorii Skovoroda University in Pereiaslav, 2021)
In the context of modern scientific, technical and information revolution, education functions as a complex socio-economic organism, which plays an important role in the progress of mankind. The state policy in the field of education is an integral part of the state policy. Everything that happens in society, economy, culture, one way or another, affects the formation and implementation of educational policy, the functioning of the education system as a whole. The aim of the article is to highlight the essence of the "multimedia" concept, "multimedia technologies" and "distance learning", the characteristics of the types of multimedia products that are most often used to study theoretical material, revealing the benefits of using multimedia technologies in the educational environment. The article reveals the essence of concepts: "multimedia", "multimedia technologies" and "distance learning", describes the types of multimedia products that are often used to organize the study of theoretical material, discloses the advantages of using multimedia technologies in the educational environment, identifies the main methodological and didactic requirements to the use of multimedia technologies in training at a higher education institution. Conclusions: using multimedia technologies allows to individualize the learning process and promotes the independence of applicants. Thanks to these technologies, the interest of applicants in the educational component increases, there is confidence that he is able to learn it, by re-studying the material at a convenient time. It is also possible to adjust the time and duration of training to your own schedule and capabilities.